Modernizing Our Understanding of Total Hip Arthroplasty in the Pediatric and Young Adult Patient: A Single-center Experience. Issue 4 (19th April 2023) - Whitmarsh-Brown, Meghan A.; Christ, Alexander B.; Lin, Adrian J.; Siddiqui, Ali A.; Herman, Renee Y.; Allison, Daniel C.; Goldstein, Rachel Y.
Abstract : Introduction: Pediatric hip disorders represent a broad range of pathology and remain a significant source of morbidity for children and young adults. Surgical intervention is often required for joint preservation, but when salvage is not possible, joint replacement may be indicated to eliminate pain and preserve function. Although there have been significant updates in the management of both pediatric hip disease and the field of total hip arthroplasty (THA), there is a paucity of literature reflecting advancements in the area of pediatric and young adult (PYA) arthroplasty. No study has investigated the impact of approach on outcomes after PYA THA. The purpose of this study is to describe the indications, techniques, and early outcomes of THA in the PYA population in a modern practice setting. Methods: We performed a retrospective descriptive analysis of all patients undergoing primary THA performed at a tertiary care children's hospital from 2004 to 2019. Ninety-three hips in 76 patients were evaluated. Demographics, intraoperative variables, postoperative pain and function ratings, and complication and revision rates were collected. Results: Eighty-five hips in 69 patients were included. Patients were aged 12 to 23 years old, with males and females represented equally (33 vs. 36, respectively). The most common cause of hip pain was avascular necrosis (AVN, 56/85, 66%), most commonly due to slipped capital femoral epiphysis (13/56, 23%) idiopathic AVN (12/56, 21%), and chemotherapy (12/56, 21%). Half of all hips had been previously operated before THA (43/85). Thirty-six procedures were performed via the posterolateral approach (36/85, 42%), 33 were performed via direct anterior approach (33/85, 39%), and 16 were performed via the lateral approach (LAT, 16/85, 19%). At final follow-up, 98% (83/85) of patients had complete resolution of pain, 82% (70/85) had no notable limp, and 95% (81/85) had returned to all activities. There were 6 complications and 1 early revision. Average Hip disability and Osteoarthritis Outcomes Score for Joint Replacement scores increased by 37 points from 56 to 93. The overall revision-free survival rate for PYA THA was 98.8% (at average 19-mo follow-up). Conclusions: Modern PYA THA is dissimilar in indications and surgical techniques to historic cohorts, and conclusions from prior studies should not be generalized to modern practice. In our practice, PYA patients most commonly carry a diagnosis of AVN, and THA can be performed with modern cementless fixation with large cup and head sizes and ceramic-on-cross-linked polyethylene bearings utilizing any approach. Further study is required to better characterize middle-term and long-term results and patient-reported outcomes. Level of Evidence: Therapeutic Level IV—retrospective case series.